Balanced and transient aspects of the intertropical convergence zone - Gonzalez, Alex O., author; Schubert, Wayne H., advisor; Maloney, Eric D., committee member; Birner, Thomas, committee member; Estep, Donald J., committee member (Colorado State University. Libraries, 2015)
The Intertropical Convergence Zone (ITCZ) is one of the primary drivers of tropical circulations and because of its interactions with the extratropics, contributes significantly to Earth's general circulation. This dissertation investigates dynamical aspects of the ITCZ using a variety of analytical and numerical models. In the first chapter, we learn that deep and shallow balanced Hadley circulations are forced by deep diabatic heating and Ekman pumping at the top of the boundary layer, respectively. Also, when the ITCZ is located off of the equator there is an inherent asymmetry between the winter and summer Hadley cells due to the anisotropic nature of the inertial stability. The second study examines shallow and deep vertical motions over the eastern Pacific Ocean (80°W--150°W) using the Year of Tropical Convection reanalysis (YOTC). Vertical motions in the eastern Pacific tend to be bimodal, with both shallow and deep vertical motions occurring throughout the year. Shallow vertical motions are typically narrow and restricted to low latitudes (ITCZ-like) while deep vertical motions tend to be broad and are located poleward of shallow regimes, except during El Niño conditions. The study of balanced Hadley circulations is also extended to investigate the role of transient aspects of the Hadley circulation. The solutions illustrate that inertia-gravity wave packets emanate from the ITCZ and bounce off a spectrum of turning latitudes when the ITCZ is switched on at various rates. These equatorially trapped wave packets cause the Hadley cells to pulsate with periods of 1--3 days. In the last part of this dissertation, we focus on boundary layer aspects of the formation of the ITCZ. Since the ITCZ boundary layer is a region of significant meridional convergence, meridional advection should not be neglected. Using a zonally symmetric slab boundary layer model, shock-like structures appear in the form of near discontinuities in the horizontal winds and near singularities in the vorticity and Ekman pumping after 1--2 days. The numerical model also agrees well with dynamical fields in YOTC while adding important details about the boundary layer pumping and vorticity. In closing, we believe that the ITCZ is a highly transient region vital to the general circulation of the atmosphere, and many of its features can be explained by dry dynamics.
Keywords: boundary layer; ITCZ; Hadley circulation; atmospheric dynamics